In Search of 'National Memory': The Politics of History, Nostalgia and the Historiography of Communism in the Czech Republic - Kopeček, Michal (Dějiny – teorie – kritika, 2007)
Based on the discussions around the proposed establishment of the Institute of National Memory in the Czech Republic, the article aims to surpass the narrow political conflict and instead to analyze what does this mean for the historiography of recent history and the historical culture in general. It starts by examining the role and achievements of the historical profession vis-à- vis the societal and political dealing with the legacy of the communist dictatorship after 1989. In this period, the historiography was significantly determined by the rehabilitation of the nation-state in the political realm and by the process of democracy building, with the obvious need to legitimize the existence of both. The study focuses on how this is linked to the concept of national history and how it relates to the internal restructuring and development of the historiography of recent history as well as the “upsurge of memorialism” in the recent decades. After analyzing the new wave of politization of contemporary history in East Central Europe during the last few yeas, it concludes with a section concerning the role and potential implications of the institutes of national memory in the region. The study concentrates mainly on the Czech developments, attempting however to draw a broader picture and to base the conclusions on comparisons with other countries in the region, primarily Poland.